The Uygur- Turkic Biography of the seventh-centruy Chinese Buddhist Pilgrim xuanzang, ninth and tenth chapters edited and translated with a commentary(Kahar Barat). - Wilkens, Jens.
Ural Altaische Jahrbücher, 19 (2005) 263-266 ss.